Salmonella sp. Contamination Detection in Layer Chicken Eggs Traded in Traditional Market of Medan Johor District - L. Riski; Y. Yunilas; U. Hasanah; L. Warly; E. Yusni; M. I. A. Nasution (Jurnal Sain Peternakan Indonesia, 2023)
Salmonella sp. can contaminate layer chicken eggs and cause salmonellosis. This study aims to determine whether there is contamination by Salmonella sp. in layer chicken eggs traded in traditional markets of Medan  Johor District. Sampling locations were determined by purposive sampling, including Kwala Bekala Market, Johor Market, and Tikung Market, with 90 samples. The working procedures included isolating bacteria from egg yolks using the pour plate method on SSA media, observing the bacteria morphology, calculating total Salmonella sp. colonies, Gram staining, and biochemical tests. The research results obtained indicated that the average total colonies of Salmonella sp. in Kwala Bekala Market were 1.45 x 105 CFU/g, in Johor Market they were 5.8 x 104 CFU/g, and in Tikung Market they were 3.6 x 104 CFU/g. The colony morphology of Salmonella sp. is circular and colourless, with a black spot in the center. The Salmonella sp. bacteria are Gram-negative with a red color, and are bacilli. Biochemical tests showed indole (-), MR (+), VP (-), SCA (+), and TSIA (+) test results. Based on the study results, it can be concluded that 4.44% of the positive samples were contaminated with Salmonella sp. in the traditional market of Medan Johor District and exceeded the BMCM in SNI 7388:2009.